Brugada ECG pattern: a physiopathological prospective study based on clinical, electrophysiological, angiographic, and genetic findings - Duthoit, Guillaume; Fressart, Véronique; Hidden-Lucet, Françoise; Simon, Françoise; Kattygnarath, Darouna; Charron, Philippe; Himbert, Caroline; Aouate, Philip; Guicheney, Pascale; Lecarpentier, Yves; Frank, Robert; Hébert, Jean-Louis (Frontiers in Physiology, 2012)
Introduction: Brugada syndrome (BrS) is considered a primary electrical disease. However, morphological abnormalities have been reported and localized arrhythmogenic right ventricular (RV) dysplasia/cardiomyopathy (ARVD/C) may mimic its phenotype, raising the question of an overlap between these two conditions and making difficult the therapeutic management of patients with borderline forms. The main objective of this study was to assess prospectively the prevalence of BrS and ARVD/C on the basis of international criteria, in patients with BrS-ECG and normal echocardiography, looking for a potential overlap between the two pathologies. The secondary objectives were to describe and quantify angiographic structural alterations, hemodynamics, electrophysiology, and genetics in the setting of BrS-ECG. Materials and Methods: Hundred and fourteen consecutive patients matched in age underwent prospectively cardiac catheterization and quantitative biventricular contrast angiography to rule out a structural heart disease. Fifty-one patients with a BrS-ECG (BrS group, 7 F, 44 M, 43 ± 11 y) had a spontaneous or ajmaline-induced BrS coved type ECG. For angiographic comparison, 49 patients with localized ARVD/C but without ST segment elevation in the right precordial leads (14 F, 35 M, 39 ± 13 y) were also studied. They fulfilled international ESC/WHF 2000 criteria and presented angiographic localized forms, mainly confined to hypokinetic anteroapical zone (characterized by trabecular dysarray and hypertrophy), and/or diaphragmatic wall, thus resulting in RV normal volumes and preserved systolic function. These two populations were also compared with 14 control patients (7 F, 7 M, 38 ± 16 y). Among BrS group, we identified three main angiographic phenotypes: BrS group I = patients with normal RV (n = 15, 29%); BrS group II = patients with segmental RV wall motion abnormalities but no structural arguments for ARVD/C (n = 26, 51%); BrS group III = patients with localized abnormalities suggestive of focal ARVD/C (n = 10, 20%). Results: Among BrS group, 34/51 patients (67%) fulfilled BrS HRS/EHRA 2005 criteria. Nineteen (37%) were symptomatic for aborted sudden death, agonal nocturnal respiration or syncope. Ventricular stimulation was positive in 14 patients (28%). Angiography showed RV abnormalities in 36/51 patients (71%) of BrS group (BrS groups II and III). Late potentials were present in 73% (100% sensitivity and NPV for an angiographic ARVD/C, but poor specificity and PPV, both 37%). In BrS group III, 8/10 patients (16% of BrS patients) finally fulfilled international ESC/WHF 2000 ARVD/C criteria and 5/10 (10% of BrS patients) fulfilled BrS diagnostic criteria. An overlap was observed in 4 patients (8% of BrS patients) who fulfilled both ARVD/C and BrS criteria. Among the 45 genotyped patients, only one presented a SCN5A mutation, whereas a TRPM4 mutation was found in another patient. Both belonged to BrS group II. MOG1 gene analysis was negative for all patients, as were PKP2, DSP, DSG2, and DSC2 analyzes performed in BrS group III. Conclusions: Seventy-one percent of patients with a BrS-ECG had abnormal RV wall motion and 16 had structural alterations corresponding to localized (anteroapical and/or diaphragmatic) ARVD/C. Moreover, 8% of BrS-ECG patients fulfilled both BrS and ARVD/C criteria. Our results support the hypothesis of an overlap between BrS and localized forms of ARVD/C. Conversely, genetic screening was poorly contributive for both diseases in the present series.